Spatio-temporal structure of turbulent Reynolds stress zonal flow drive in 3D magnetic configuration. (16th May 2017) - Schmid, B; Manz, P; Ramisch, M; Stroth, U
Abstract: The poloidal dependence of the zonal flow drive and the underlying Reynolds stress structure are studied at the stellarator experiment TJ-K by means of a poloidal Langmuir-probe array. This gives the unique possibility to study the locality of the Reynolds stress in a complex toroidal magnetic geometry. It is found that the Reynolds stress is not homogeneously distributed along the flux surface but has a strong poloidal asymmetry where it is concentrated on the outboard side with a maximum above the midplane. The average tilt of the turbulent structures is thereby reflected in the anisotropy of the bivariant velocity distribution. Using a conditional averaging technique the temporal dynamics reveal that the zonal flow drive is also maximal in this particular region. The results suggest an influence of the magnetic field line curvature, which controls the underlying plasma turbulence. The findings are a basis for further comparison with turbulence simulations in 3D geometry and demonstrate the need for a global characterisation of plasma turbulence.